2017
DOI: 10.1590/18069657rbcs20160274
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Mineralogical Characterization of Magnetic Materials from Magnetic Soils of the Southern Espinhaço Mountain Chain and of the Upper Jequitinhonha Valley, State of Minas Gerais, Brazil

Abstract: In the Southern Espinhaço Mountain Chain and in the Upper JequitinhonhaValley, magnetic soils, in different pedogenetic stages, are found to be forming over intrusions of basic lithology. The essential chemical and mineralogical properties of samples from magnetic soil profiles from those two physiographic environments in the state of Minas Gerais, Brazil, are reported. Three of the pedons (Rhodic Kandiustox -RKox, Rhodic Haplustox -RHox, and Typic Argiustoll -TAoll) were identified as being indeed developed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In the forest soils, where no herbicide and no fertilization are applied, Al levels were higher compared to the other agricultural systems (Table 2), since Al is one of the most persistent elements in highly weathered tropical soils without fertilization (Silva et al, 2017). Due to its high potential acidity, NF also presented a higher potential CEC than the other land use systems evaluated (Table 2).…”
Section: Soil Chemical Analysesmentioning
confidence: 93%
“…In the forest soils, where no herbicide and no fertilization are applied, Al levels were higher compared to the other agricultural systems (Table 2), since Al is one of the most persistent elements in highly weathered tropical soils without fertilization (Silva et al, 2017). Due to its high potential acidity, NF also presented a higher potential CEC than the other land use systems evaluated (Table 2).…”
Section: Soil Chemical Analysesmentioning
confidence: 93%
“…In contrast, the Mössbauer spectra indicated that Mh is the only ferrimagnetic Fe oxide in the sand fraction of most soils, with the exception of LV 7 and LV 11 , where highly oxidized Mt traces, {Fe}/[Fe] lower than 1.88 (Vandenberghe et al, 2000), were identified. Silva et al (2017) also observed only Mh in Oxisols with spontaneous magnetism investigated by the Mössbauer spectroscopy.…”
Section: Mineralogical Studymentioning
confidence: 85%
“…Rhodic Oxisols exhibit strong magnetic attraction due to high contents of ferrimagnetic Fe oxides (maghemite and magnetite) (Costa et al, 1999(Costa et al, , 2014Camêlo et al, 2018;Poggere et al, 2018). These minerals have often been used in studies on pedogenesis (Silva et al, 2017;Camêlo et al, 2018) for stratification of environments (Ramos et al, 2017) and soil fertility (Costa et al, 2018) in Brazil and elsewhere in the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low silt/clay ratio in Oxisols is related to its advanced stage of weathering [12]. Silva et al [13] also found low ratio when studied soils originated from metabasalt in another region of Brazil.…”
Section: Soil Characterisation and Mineralogical Analysismentioning
confidence: 99%